Experimental quantitative evaluation of thermal performance in refrigerated displays case with variation of the thickness of the air curtain and perforation density of the back panel - Nascimento, Samuel Mariano do (2013)
Open multideck display cabinets are widely used to expose perishable products in supermarkets and convenience stores. This paper reports the results of experimental tests performed according to ISO23953 in a open multideck refrigerated display cabinet to assess the impact on the thermal performance by varying the width of the discharge air grille and the perforation density of the back panel. The experimental laboratory tests were conducted for climate class n.° 3 (25° C and 60%). The results evaluation shows that the perforation density of the back panel and the width of discharge air grille alter significantly the thermal entrainment factor and the energy consumption of the equipment. The best performance configuration showed a 10% reduction of the cooling load. The analysis of the results provides valuable information for the development of these equipments.